2021
DOI: 10.1080/24750263.2021.1918275
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the role of past and current climate in shaping the distribution of two parapatric European bats, Myotis daubentonii and M. capaccinii

Abstract: In this contribution, we aim at determining the role of climate in shaping the current and historical (Last Glacial Maximum and Middle Holocene) distributions of two parapatric bat species (Myotis daubentonii and Myotis capaccinii) in Europe, using ensemble Habitat Suitability Modelling (HSM). Model projection to current climatic conditions predicted distributions largely coherent with the ones observed for the two species in the study area. Temperature-and precipitation-linked variables well accounted for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…While low-flying bat species in our study area may have adapted to dry conditions [ 96 ], they still depend on patches of evergreen vegetation and tree cover to maintain prey abundance and support bat populations [ 97 , 98 ]. Several studies have already shown that the ongoing climate change has deleterious effects on the distribution of many species in some parts of the world [ 99 , 100 ] and has altered the migration patterns and reproductive timing of others [ 99 , 101 , 102 ]. ASALs in Africa may not be an exception.…”
Section: Discussionmentioning
confidence: 99%
“…While low-flying bat species in our study area may have adapted to dry conditions [ 96 ], they still depend on patches of evergreen vegetation and tree cover to maintain prey abundance and support bat populations [ 97 , 98 ]. Several studies have already shown that the ongoing climate change has deleterious effects on the distribution of many species in some parts of the world [ 99 , 100 ] and has altered the migration patterns and reproductive timing of others [ 99 , 101 , 102 ]. ASALs in Africa may not be an exception.…”
Section: Discussionmentioning
confidence: 99%
“…Our bat distribution database comprised of the data used in recently published studies 76 , recent Global Diversity Information Facility (GBIF) data 77,78 , and the Darkcide database 79 . The Darkcide database included recent data collected by bioacoustic surveys in Chiang Mai and Kanchanaburi in Thailand by A.C. Hughes using an echometer Pro, and multiple published datasets [76][77][78][80][81][82][83][84][85][86][87][88] . The data was integrated as we attempt to keep the database complete, even if not all data is used within our particular study.…”
Section: Modeling Of Bat Distributionsmentioning
confidence: 99%
“…level = 3; RF: n.trees = 10,000, bag.fraction = 0.75, shrinkage = 0.001. Then, the 'BIOMOD_ Modeling' function was used to calibrate the single models, and the 'BIOMOD_Ensemble-Modeling' algorithm was subsequently run to obtain the Ensemble models, using as input only single models with high performance (AUC > 0.8 and TSS > 0.7) (Cerasoli et al 2019;De Simone et al 2020;Di Gregorio et al 2021). We chose the 'wmean' algorithm to merge single models, as it averages models into the Ensemble one based on a weighted mean function, in which weights are the discrimination scores (Thuiller et al 2016).…”
Section: Ecological Niche Modellingmentioning
confidence: 99%